Los guerrilleros de Dios: “¿Cómo ser cristianos y cubanos a la vez?”. Etnografía del pentecostalismo en La Habana postsoviética (2017-2019) - Flore Pavy (Nuevo mundo - Mundos Nuevos, 2025)
The objective of this article is to take a new look at the social, economic, political and ideological changes that occurred in Cuba after the collapse of the Soviet bloc, through the still little explored prism of the accelerated development of Pentecostal churches in Havana. Starting from an analysis of the post-revolutionary Protestant spaces of worship that flourish in the west of the country and particularly in its capital, the aim is to describe the local forms of liturgy marked by a sudden and massive charismatic turn. These liturgies are largely inspired by North American evangelical rites imported by foreign pastors through international training networks, but they also incorporate various indigenous elements taken in particular from the ritual codes of possession cults, as well as certain specific motifs of the revolutionary rhetoric. Particularly active and dynamic -"at war"-, these churches carry out vast evangelization campaigns in the poor neighborhoods of Havana and in the marginal provinces of the country.